The changing landscape of agriculture in Ghana: Drivers of farm mechanization and its impacts on cropland expansion and intensification - Houssou, Nazaire; Chapoto, Antony (International Food Policy Research Institute, 2014)
This study assesses whether the recent public and private efforts to improve farmers’ access to mechanical power in Ghana have had the intended effects on the country’s agricultural sector. Using panel survey data, this paper analyses the drivers of farm mechanization and its net impacts on cropland expansion and farming system intensification in northern Ghana. Several factors explain the use and use intensity of agricultural mechanization, including landholding size, total labor and fertilizer use per hectare, chemical use, and amount of land left fallow. More importantly, the results suggest that farm mechanization did have a positive impact on cropland expansion during the survey period. The results presented here support the existence of a labor substitution effect resulting from tractor use.